The influence of digital marketing on performance of e-retailing business in Thailand - Phusalux , jongdee (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purpose of this research was to study a model of factors influencing the performance of e-retailing business in Thailand direct influence. Indirect and total influence of variables on the performance of online retail business in Thailand and to propose the model of performance of e-retailing business in Thailand. A total of 240 e-retailing business entrepreneurs in Thailand were included in sample. The research instrument was a 7-level rating scale questionnaire, and the data were analyzed using Structural Equation Modeling (SEM). The results showed that the structural equation model was in harmony with the empirical data. Chi-square = 49.781, df = 38, p = .096, CMIN/DF ( /df) = 1.310, GFI=.972, CFI=.995, AGFI=.942, RMR=.012 and RMSEA=. .033 The results of the benchmark analysis concluded that the digital marketing model, customer relationship management and data-driven marketing influences the performance of e-retailing business in Thailand. In the age of the digital society and rapidly changing technology, entrepreneurs may employ marketing aspects and adjustments for business performance, as well as strategically changing organizational style to help create value for customers and the organization.